2021
DOI: 10.1039/d1ay00481f
|View full text |Cite
|
Sign up to set email alerts
|

Can a field molecular diagnosis be accurate? A performance evaluation of colorimetric RT-LAMP for the detection of SARS-CoV-2 in a hospital setting

Abstract: SARS-CoV-2 currently represents a serious global public health problem. Non-pharmaceutical intervention measures (NPIs) have been widely adopted, and the testing strategy since the beginning of the infection is the most...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 45 publications
0
6
1
Order By: Relevance
“…The detection limit of 4.8 × 10 4 copies (Ct ~ 22.93) found in the present study is higher than those reported in the literature 24 27 , 34 . Nonetheless, it has excellent potential for the confirmatory diagnosis of the VOC Gamma.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…The detection limit of 4.8 × 10 4 copies (Ct ~ 22.93) found in the present study is higher than those reported in the literature 24 27 , 34 . Nonetheless, it has excellent potential for the confirmatory diagnosis of the VOC Gamma.…”
Section: Discussioncontrasting
confidence: 81%
“…The reaction was incubated at 65 °C for 70 min in a ProFlex 3 × 32-well PCR System (Thermofisher, Massachusetts, USA). The WarmStart Colorimetric Assay uses phenol red as an indicator of target amplification, and the color of the reaction changes from pink to yellow in the presence of amplicons (Silva et al 34 ). After amplification, we analyzed the color of the tube visually and confirmed it by agarose gel electrophoresis.…”
Section: Methodsmentioning
confidence: 99%
“…POCTs rely on low budget solutions to proportionate wide access to essential diagnosis needs, turning these type of tests very useful in the pandemic scenery ( Silva et al., 2021 ). However, despite countless works devoted to demonstrate the ability of NAAT-based approaches to be used as POCTs, the wide number of solutions wasn´t enough to dislodge RT-qPCRs as the prime choice for performing SARS-CoV-2 detection ( Bustin et al., 2021 ).…”
Section: Conclusion and Near Future Perspectivesmentioning
confidence: 99%
“…RT-qPCR joins very high sensivity, good specificity and was successfully adapted to the screening of large numbers of samples, what contributed for the implementation of the technique as the gold-standard for SARS-CoV-2 detection and COVID-19 management ( Nörz et al., 2020 ). Isothermal nucleic acid amplification has been intensively explored for point-of-care tests (POCTs) ( Bektaş et al., 2021 ), although being also used in clinical settings, but continues to be less appealing than RT-qPCR ( Silva et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…From the perspective of point-of-care tests (POCT), loopmediated isothermal amplification (LAMP) received great attention, especially after the COVID-19 pandemic, when it was widely used as an alternative technique to PCR to obtain diagnoses faster and cheaper. [28][29][30][31] Initially, methodologies RT-LAMP used primers designed to recognise well-conserved regions of the virus and thus could indiscriminately detect any variant, which is very important for a common diagnostic test. Recently, RT-LAMP methodologies have emerged with the opposite strategy, using primers designed to identify specific lineage-defining mutations.…”
Section: Introductionmentioning
confidence: 99%